PENGEMBANGAN E-JOBSHEET PERAWATAN SISTEM REM TROMOL MATA PELAJARAN SASIS DAN PEMINDAH TENAGA - Diki Setiawan; Setuju; Samsul Hadi (JURNAL VOKASI DEWANTARA (JVD), 2025)
This study aims to produce an E-Jobsheet for drum brake system maintenance and findout its feasibility. This research uses research and development methods of 4D models,including Define, Design, Develop and Disseminate. The research was conducted at SMKTamansiswa Jetis Yogyakarta.. The data collection techniques used are interviews,observations, questionnaires. The result of this study is . E-Jobsheet entitled ". E-JobsheetDrum brake system maintenance for class XI". E-Jobsheet can be accessed via the link:https://heyzine.com/flip-book/24271e6200.html.